Development of an online ecological data warehouse / Cham Hui - Cham, Hui (2016)
Effective and efficient maintenance and monitoring of tropical water bodies such as lakes, reservoirs and river requires well-documented, validated, and coherent data archives. Data are collected and stored individually and this makes data integration difficult even among close collaborators. Ecological data warehouses for data mining require individual databases that are precisely explained with validated metadata. A data warehouse system for tropical water bodies should have a standard interface and identical ways of representing biological data for data exchange. These can solve the problems of incomplete data, data standardization and data sharing. The data warehouse prototype developed in this study comprises of graphical user interface (GUI) developed using ASP.Net. To facilitate data integration and exchange, standard format and common data exchange method via web services are used. XML, which is known for its high degree of interoperability for data exchange and transfer, is used to represent metadata. Darwin Core is used for formats for ecological and biological data management and for data exchange protocol. The data warehouse system prototype developed in this study aims to provide information management of hydrological and ecological data on Malaysian water bodies with interactive user interface, report generation, data support for data mining tools, and data sharing between water research and management agencies.